Aspirations undone: hydropower and the (re) shaping of livelihood pathways in northern Laos - Suhardiman, Diana; Rigg, J. (Springer, 2021)
This paper looks at how local livelihoods and to a certain extent their transitions are embedded in, and in thrall to, power relations at higher levels. Placing the (re)shaping of livelihood pathways within the context of top-down hydropower planning, it shows how the latter predetermines farm households’ current farming strategies and future livelihood pathways. Taking two villages along the Mekong River, both of which are to be impacted by the planned Pak Beng hydropower dam in Pak Beng district, Oudomxay province, the paper illustrates how the pathways that rural livelihoods are taking in northern Laos are being shaped by decisions and processes embedded in national and regional exigencies. We argue that top-down approaches in hydropower planning, as manifested in the current institutional vacuum to formally deal with resettlement and compensation issues at the village level result in village authorities’ and potentially affected villagers’ inability to strategically convey and negotiate their views and concerns. Moreover, we reveal how it is the specter of change which drives livelihood adaptation, not change itself, thus illustrating how the defined compensation rules and procedures (re)shape farm households’ farming strategies and future livelihood pathways even prior to the construction of the hydropower dam.